Reputation and power: organizational image and pharmaceutical regulation at the FDA - Carpenter, Daniel P (Princeton studies in American politics, 2014)
The U.S. Food and Drug Administration is the most powerful regulatory agency in the world. How did the FDA become so influential? And how exactly does it wield its extraordinary power? Reputation and Power traces the history of FDA regulation of pharmaceuticals, revealing how the agency's organizational reputation has been the primary source of its power, yet also one of its ultimate constraints.